RESPON HORMONIK LUPIS SAKUCA TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI BESAR (Capsicum annuum L.) - Suci Melinia Aryanti; Siska Nuramelia; Retna Andriani; Tati Hariyati (Musamus University, 2019)
Waste that is very much in the environment makes eyesight not good and environmental health becomes less good can even lead to environmental pollution, to cope with so much waste that can be done to process waste that can still benefit the environment, one of which is by making hormones from natural materials that are not used or even become waste. This study aims to determine the hormonal response of LUPIS SAKUCA to the growth and production of large chilies. In this research, extracts from unused natural ingredients are used, namely banana peels, eggshells and coconut fiber with large chili plants as the responsive objects. Group A (normal control) was not given hormone extract, group B was given 10% hormone extraction, group C was given 20% hormone extraction, group D was given 30% hormone extraction, and data on the effect of extraction was done with the RAL system. Analysis of RAL data that was highly influential was evident in plants 14 and 21 HST, while the extraction of hormones in plants with 7 HST did not significantly affect the large chili plants